Plant Functional Groups Dominate Responses of Plant Adaptive Strategies to Urbanization - Xiao, Yihua; Liu, Shirong; Zhang, Manyun; Tong, Fuchun; Xu, Zhihong; Ford, Rebecca; Zhang, Tianlin; Shi, Xin; Wu, Zhongmin; Luo, Tushou (Frontiers in Plant Science, 2021)
ABSTRACT Urbanization causes alteration in atmospheric, soil and hydrological factors and substantially affects a range of morphological and physiological plant traits. Correspondingly, plants might adopt different strategies to adapt to urbanization promotion or pressure. Understanding of plant traits responding to urbanization will reveal the capacity of plant adaptation and optimize the choice of plant species in urbanization green. In this study, four different functional groups (herbs, shrubs, subcanopies and canopies, eight plant species totally) located in urban, suburban and rural areas were selected, and eight replicated plants were selected for each species at each site. Their physiological and photosynthetic properties and heavy metal concentrations were quantified to reveal plant adaptive strategies to urbanization. The herb and shrub species had significantly higher starch and soluble sugar contents in urban than in suburban areas. Urbanization decreased the maximum photosynthetic rates and total chlorophyll contents of the canopies (Engelhardtia roxburghiana and Schima superba). The herbs (Lophatherum gracile and Alpinia chinensis) and shrubs (Ardisia quinquegona and Psychotria rubra) species in urban areas had significantly lower nitrogen (N) allocated in cell wall and leaf δ 15N values but higher heavy metal concentrations than those in suburban areas. The canopy and subcanopy (Diospyros morrisiana and Cratoxylum cochinchinense) species adapt to the urbanization via reducing resource acquisition but improving defence capacity, while the herb and shrub species improve resource acquisition to adapt to the urbanization. Our current studies indicated that functional groups affected the responses of plant adaptive strategies to the urbanization.